The impact of fintech and digital financial services on financial inclusion in India - Mohammad Asif; Mohd Naved Khan; Sadhana Tiwari; Showkat K. Wani; Firoz Alam (Journal of Risk and Financial Management, 2023)
India's financial inclusion has significantly improved during the last several years. In recent years, there has been a rise in the number of Indians who have bank accounts, with this figure believed to be close to 80% at present. Fintech businesses in India are progressively becoming more noticeable as the Government of India (GoI) continues to strive for expanding financial services to the underbanked sector of the population. To reach the underbanked segments of the population and provide a stable operating environment for fintech businesses, India must seek to increase financial inclusion. In this study, regression and correlation were employed, together with secondary data gathered from the RBI, to analyze this influence. The aim was to determine the impact of fintech and digital financial services on financial inclusion in India. According to the results, fintech businesses have significantly aided financial inclusion in this nation, especially for the middle class. These findings will be helpful for policy-makers working hard to bring every individual in this country into an organized financial system.
Keywords: 650; behavioral intention; financial inclusion; financial services; fintech; service trust; social influence; usability